The use of information for management decision-making of executives, Faculty of Education, Bangkokthonburi University - Tesmuang, Rawisuda; Onamornrat, Rossarin (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
This research aims to 1) study the level of information management, 2) study the use of information in administrative decision making, and 3) analyze the relationship between information management and administrative decision making of administrators of the Faculty of Education, Bangkokthonburi University, using questionnaires as a data collection tool and analyzing with descriptive statistics and Pearson correlation coefficient. The research results found that 1) the overall level of information management was at a high level (x̄ = 4.12), with the highest level being information quality (x̄ = 4.35) and the lowest level being information dissemination and access (x̄ = 3.78). 2) the level of data utilization in administrative decision-making was at a very high level (x̄ = 4.18), with the highest level being strategic and policy planning (x̄ = 4.36) and the lowest level being organizational evaluation and development (x̄ = 3.84). 3) The relationship between information management and administrative decision-making was found to be highly positive and statistically significant at the .01 level (r = 0.721, p < .01). The study findings demonstrate that effective information management, particularly in the areas of data quality and strategic planning, significantly enhances management decision-making among administrators in educational organizations. A centralized information system should be developed to enhance access to and utilization of data more comprehensively and sustainably. Article history: Received 10 February 2025 Revised 14 July 2025 Accepted 18 July 2025 SIMILARITY INDEX = 0.78 %